A Randomized, Double‐Blind, Placebo‐Controlled Study of Gelesis100: A Novel Nonsystemic Oral Hydrogel for Weight Loss. Issue 2 (13th November 2018) - Greenway, Frank L.; Aronne, Louis J.; Raben, Anne; Astrup, Arne; Apovian, Caroline M.; Hill, James O.; Kaplan, Lee M.; Fujioka, Ken; Matejkova, Erika; Svacina, Stepan; Luzi, Livio; Gnessi, Lucio; et al.
Abstract : Objective: This study aims to assess the efficacy and safety of Gelesis100, a novel, nonsystemic, superabsorbent hydrogel to treat overweight or obesity. Methods: The Gelesis Loss Of Weight (GLOW) study was a 24‐week, multicenter, randomized, double‐blind, placebo‐controlled study in patients with BMI ≥ 27 and ≤ 40 kg/m 2 and fasting plasma glucose ≥ 90 and ≤ 145 mg/dL. The co‐primary end points were placebo‐adjusted weight loss (superiority and 3% margin super‐superiority) and at least 35% of patients in the Gelesis100 group achieving ≥ 5% weight loss. Results: Gelesis100 treatment caused greater weight loss over placebo (6.4% vs. 4.4%, P = 0.0007), achieving 2.1% superiority but not 3% super‐superiority. Importantly, 59% of Gelesis100‐treated patients achieved weight loss of ≥ 5%, and 27% achieved ≥ 10% versus 42% and 15% in the placebo group, respectively. Gelesis100‐treated patients had twice the odds of achieving ≥ 5% and ≥ 10% weight loss versus placebo (adjusted OR: 2.0, P = 0.0008; OR: 2.1, P = 0.0107, respectively), with 5% responders having a mean weight loss of 10.2%. Patients with prediabetes or drug‐naive type 2 diabetes had six times the odds of achieving ≥ 10% weight loss. Gelesis100 treatment had no apparent increased safety risks. Conclusions: Gelesis100 is a promising new nonsystemic therapy for overweight and obesity with a highly desirable safety and tolerability profile.